Branchial Na+:K+:2Cl-cotransporter 1 and Na+/K+-ATPase a-subunit in a brackish water-type ionocyte of the euryhaline freshwater white-rimmed stingray, Himantura signifer - Ip, Y.K. (2014)
10.3389/fphys.2013.00362